Male teachers in primary school - Giuseppe Zanniello (Firenze University Press, 2019)
In OECD member countries, primary school teachers form a minority of the teaching staff due to the low remuneration, the low social prestige and also due to the fact that it has been considered as a profession for women. As, for pedagogical reasons primary school students need to relate both with female and male teachers, measures have been taken in several countries to improve the image of the teaching profession among men. It was assumed that four training initiatives for university students enrolled in the primary education course (interviews with students, interviews with teachers, film club on the teacher, meetings with teachers) would have helped increasing students' task awareness; strengthening their motivation for course attendance; providing arguments to dismantle the social prejudices and stereotypes about teaching profession. In this paper, the training activities and the data collection methods are being described. The results confirm the validity of the activities carried out which are to be integrated with new activities that could start even before the university studies.   Maestri maschi nella scuola primaria. Nei Paesi membri dell'OECD i maestri di scuola primaria costituiscono una minoranza del corpo docente, per la scarsa remunerazione, lo scarso prestigio sociale e lo stereotipo di una professione ritenuta femminile. Siccome, per motivi pedagogici, i bambini e le bambine di scuola primaria hanno bisogno di relazionarsi sia con i maestri sia con le maestre, in diversi Paesi sono state prese delle misure per migliorare l'immagine della professione presso gli uomini. Si è ipotizzato che quattro iniziative formative per i giovani iscritti al corso universitario per l'insegnamento primario (interviste a studenti, interviste a maestri, cineforum sul maestro, incontri con maestri), avrebbero accresciuto negli studenti la consapevolezza dei compiti che si preparavano a svolgere; rafforzato la loro motivazione alla frequenza del corso universitario; fornito argomenti per smontare i pregiudizi e gli stereotipi sociali circa la professione di maestro. Sono descritte le attività formative svolte e le modalità di rilevazione dei dati. Al termine della discussione dei risultati è confermata la validità delle attività svolte, da integrare con nuove attività, che potrebbero iniziare anche prima degli studi universitari.